The Effectiveness of Portofolio Assessment in English Writing Skill of Islamic Junior High School - Hafiz, Hairori Sahrul; Hakim, M Ikhwanul; Harun, Muh Alawi (Journal of Research and Educational Research Evaluation, 2021)
Seeing the observation result, the evidence from teachers' reports and final tests show that writing is the weakest aspect of students' work in English and supported by semi-structured interview given with a group of students having problem in English writing. The method was pre-experimental, and the Eighth grade of A is chosen as the sample. The findings show that there is significant difference in the mean score between students’ writing before and after treatment. It is also indicated from the result of hypothesis testing, it results in Ho is rejected because 0.000 < 0.025 (2-tailed) and based on t-test criteria, if t-test is bigger than t-table, it means that Ha is accepted and Ho is rejected. Besides students’ writing skill achievement with portfolio assessment is better than students without the assessment at the level of believe 95%. Portfolio assessment has positive correlation with students’ writing skill, it shows from the result of r-test in this study is 0.671 and the level of correlation is in the level of strong. Therefore, the assessment of teachers should have well-prepared materials, assignments, and other activities being appropriate time and it is better implemented in small class because it can be easily managed.